-6g=-5g+8

Simple and best practice solution for -6g=-5g+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6g=-5g+8 equation:



-6g=-5g+8
We move all terms to the left:
-6g-(-5g+8)=0
We get rid of parentheses
-6g+5g-8=0
We add all the numbers together, and all the variables
-1g-8=0
We move all terms containing g to the left, all other terms to the right
-g=8
g=8/-1
g=-8

See similar equations:

| -2.1a=8.4 | | 3c+7=19 | | -1/4(12x-20)=5+3x | | g-159=209 | | 6^10x*6^6x=36 | | 49-7x=9x+17 | | 531=h-73 | | -9p−5=-10p | | j/24=18 | | 0.7x+0.13=0.6x+2 | | 225=25q | | -15v=-270 | | w+388=761 | | d-22=33 | | -5-x=2x-10x | | 10-3x+2=5+7x-1 | | 3a+(180-4a)=144 | | 5x/8-3/4=x/2+x/4 | | g/25=8 | | 3k=-6/7 | | 7x-1=19-5x | | 2x-28+4x=5x-7+4x | | 3a+(4a-180)=144 | | 6y-8-6-8y=-20 | | 27=k-6 | | 3a+(4a-180)=180 | | 8x-28=20+4x | | -24=y/23 | | 40-9x=3x+64 | | 91/2=x-3/8 | | X+3=8+2x | | t+6=72 |

Equations solver categories